PUBLIC HEALTH FACILITY PROVISION IN BANDUNG CITY: A POLICY EVALUATION AND FUTURE CHALLENGES - Kurniati, Poni Sukaesih; Nurnovianti, Cici (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
The provision of public health facilities is an important aspect in maintaining the well-being of a city’s citizens. Bandung, as the centre of urbanisation and economic growth in Indonesia, is no exception to this challenge. Evaluating the policies that have been implemented and identifying future challenges is important in an effort to improve the accessibility and quality of public health services for the people of this city. This discussion aims to provide a brief overview of the context, urgency, and challenges faced in the provision of public health facilities in Bandung City. Bandung, with its growing population and high population mobility, faces many challenges in fulfilling the need for quality public health services. Evaluation of the policies that have been implemented is very important in ensuring the effectiveness and sustainability of efforts to provide public health facilities in this city. In addition, social and cultural aspects such as the lack of public awareness of the importance of health and healthy lifestyles are also an obstacle in efforts to improve the accessibility of public health facilities. To address these challenges, innovative and sustainable efforts are needed to improve the quality and accessibility of public health services in Bandung City. The proposed solutions must accommodate various stakeholders’ interests and consider the social, cultural and economic context of the city. It is hoped that this abstract can serve as a foundation for further research and the development of more effective policies to support the provision of quality and affordable public health facilities for the people of Bandung City